SAT0049 11beta-hydroxysteroid dehydrogenase type 1 regulates chronic synovitis with local and systemic complications. (12th June 2018) - Hardy, R.S.; Fenton, C.; Croft, A.; Naylor, A.; Buckley, C.D.; Lavery, G.G.; Cooper, M.S.; Raza, K.
Abstract : Background: Inflammation, local joint destruction and systemic bone loss are common complications in patients with rheumatoid arthritis (RA). We have identified that localised pre-receptor activation of glucocorticoids (GC) by the enzyme 11beta-hydroxysteroid dehydrogenase type 1 (11β-HSD1) is increased within sites of inflammation and surrounding tissues, such as synovium and bone. Whilst this greatly increases local bioavailability of cortisol, which supports resolution of inflammation, in chronic disease, GCs drive may drive catabolic pathways that contribute to joint destruction and systemic bone loss. Objectives: To determine the contribution of 11β-HSD1 activated glucocorticoids to joint destruction and inflammatory bone loss, we crossed an 11β-HSD1 null mouse onto a transgenic murine model of chronic polyarthritis (TNF-Tg) to generate TNF-tg 11bKO mice. Methods: Clinical measures of joint inflammation, mobility and behaviour were collected between 4 and 9 weeks of age. Paw swelling was determined using calliper measurements. Histology was assessed in formalin fixed sections following staining with haematoxylin and eosin, safranin O or TRAP staining. Juxta articular and systemic bone losses were measured by micro-Ct. synovitis was determined by Image J analysis of histology sections. Results: 11b-HSD1 was completely knocked out within sites of inflammation in the TNF-tg 11βKO mouse. At 9 weeks, both clinical and inflammation scores were markedly exacerbated in TNF-tg 11bKO animals relative to TNF-tg counterparts (inflammation score; TNF-tg, 4.3±2.26 versus TNF-tg 11βKO, 11.08±0.86; p<0.001). This was supported by marked increases in joint swelling and juxta articular bone loss from these animals (erosion scores, TNFtg, 5.2±0.61 versus TNF-tg 11βKO, 9.0±0.66; p<0.005). Closer examination of joint destruction revealed that the pannus was larger and more extensive within subchondral bone, whilst evidence of cartilage degradation was significantly worse in the TNF-tg 11bKO mouse (synovitis size, TNFtg, 26 763 (AU) ±3200 versus TNF-tg 11βKO, 530276±3225; p<0.005). Systemic bone loss determined by bone volume to tissue volume (BV/TV), trabecular thickness (TT) and trabecular number (TN) was also greatly exacerbated within the TNF-tg 11bKO mouse (TNF-tg, BV/TV 5.7±0.75, TT 73.5±6.4, TN 0.00077±0.00004 versus TNF-tg 11βKO BV/TV 1.8±0.36, TT 7359.77±3.7, TN 0.0003±0.00005; p<0.001, p<0.005, p<0.001 respectively). Conclusions: This study demonstrates that rather than contributing to catabolic pathways of tissue destruction, local GC activation by 11b-HSD1 is critical in mediating the suppression inflammation, joint destruction, synovitis and inflammatory bone loss in this murine model of chronic polyarthritis. Acknowledgements: We would like to thank Professor George Kollias (Hellenic Pasteur Institute, Athens, Greece) for providing the hTNFtg mice. This research was supported by the Arthritis Research UK grants (Reference: 19859 and 20843). Disclosure of Interest: None declared